PENGARUH PELAKSANAAN CERAMAH DENGAN DUKUNGAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP WANITA PEKERJA SEKS LANGSUNG UNTUK PENCEGAHAN PENULARAN HIV/AIDS - Salakory, David Marthen; Wattimena, Demsi (Istek Widuri Jakarta, 2018)
This research is based on the general public concern about HIV/AIDS which has developed into a social phenomenon that worries many families, especially in Ambon City. Increasing the amount of distribution is very disturbing because the prevalence rate continues to increase from year to year. This condition should not be allowed because HIV/ AIDS is a phenomenon of iceberg, meaning that one case can be reported to represent so many people with the same case. Prevention efforts through the promotion of health have been conducted in Ambon City by various parties through lectures and distribution of leaflet or brochures at the localization of Wanita Pekerja Seks Langsung (WPSL) Tanjung Batu Merah Kota Ambon, with the aim of having knowledge and attitude change to prevent risk of HIV/ AIDS transmission. In principle, everyone has the right to gain knowledge in order to protect themselves and others. However, in reality the prevalence of HIV/AIDS in Maluku generally and specifically Ambon City remains high. Actually the risk of transmission can be reduced if the WPSL as a community at high risk can do the prevention of transmission it self. Tipe this study is quantitative, using statistical test methods.Technique of collecting data of this research use closed questionnaire, with scale measurement of knowledge and attitude measurement scale. Data were analyzed with computer program of SPSS version 20 with significance level P= 0,05 to test hypothesis for achievement of research purpose. Based on the research results can be concluded that there is correlation value of 39.6% of knowledge on changes in attitude of WPSL. While the implementation of lectures with leaflet support gave a significant effect of 60.4% on knowledge and attitude of WPSL for prevention of HIV / AIDS transmission.